Operations Research Proceedings 2014 Selected Papers of the Annual International Conference of the German Operations Research Society (GOR), RWTH Aachen University, Germany, September 2-5, 2014 - Lübbecke, Marco; Koster, Arie M.C.A; Letmathe, Peter; Madlener, Reinhard; Peis, Britta; Walther, Grit (Operations Research Proceedings, GOR (Gesellschaft für Operations Research e.V.),, 2016)
This book contains a selection of refereed papers presented at the "International Conference on Operations Research (OR 2014)", which took place at RWTH Aachen University, Germany, September 2-5, 2014. More than 800 scientists and students from 47 countries attended OR 2014 and presented more than 500 papers in parallel topical streams, as well as special award sessions. The theme of the conference and its proceedings is "Business Analytics and Optimization".